Multi-sensor data fusion in mobile devices for the identification of Activities of Daily Living - Pires, Ivan Miguel Serrano (2018)
Submitted by Paulo Pessoa (pfep@ubi.pt) on 2018-12-10T10:55:23Z No. of bitstreams: 1 PhDThesis_Ivan Pires_Final.pdf: 19881474 bytes, checksum: e922b818a644aeecbb007bef82a10690 (MD5)